BERTEOLOGI DALAM KONTEKS INDONESIA YANG MULTIKULTURAL - Puplius Meinrad Buru (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article aims at introducing the content and purpose of the Apostolic Constitution Veritatis Gaudium (Joy of Truth), namely the renewal of theological faculties and ecclesiastical institution of higher education. This renewal needs to be brought into the public sphere, so that it can be realized by paying attention to the sociocultural context of the local Church. By analyzing qualitatively data collected through the study of literature and employing the contextual theological approach, it is concluded that the Catholic Church in Indonesia, especially the theological faculties as well as Catholic higher education institutions need to intensify dialogue in theology and in preaching, to build solidarity, networking and interand trans-disciplinary cooperation with other institutions. Through dialogue theology will be more context-oriented and the preaching will be an invitation to others to deepen God’s self-revelation in the history, culture and the local social context. In this way, the Gospel or the Good News would be Joy of Truth (Veritatis Gaudium) for all people. Keywords: Veritatis Gaudium, the joy of truth, contextual theology, theology and culture, church in Indonesia, multicultural, dialog, catholic education.